The Influence of Psychological Capital, Job Satisfaction, and Employee Engagement on Job Performance on Employees of Freight Forwarder Companies In Jakarta - Aseanty, Deasy; Anggriani , Andi Suci (Eduvest - Journal of Universal Studies, 2023)
The purpose of this research is to analyze how the effect of psychological capital, job satisfaction, and employee engagement on job performance of employees at freight forwarder company in Jakarta which have branches in Semarang and Surabaya. Data were collected from 107 employees who were still actively working with a non-probability sampling technique using a purposive sampling method. The data analysis method used is regression with SPSS software version 25. The results of testing the hypothesis in this study show that there is a positive effect of psychological capital on job performance, a positive effect of job satisfaction on job performance, and a positive effect of employee engagement on job performance. The results of this study are expected to provide input for managers to improve job performance variables by maintaining levels of psychological capital, job satisfaction, and employee engagement among employees at the freight forwarder company.